Development of computer aided clamping system design for workpieces with freeform surfaces. (February 2018) - Nategh, Mohammad Javad; Parvaz, Hadi
Abstract: The development of computer aided fixture design has already encountered numerous mathematical and technical challenges having hampered realization of automated design of fixturing system consisting of locating and clamping systems. This is more critical for workpieces of freeform surfaces compared with those of polyhedral geometry. In the present study, the mathematical foundation of clamping system design has been developed by using the concept of screw theory and the minimum norm principle. An algorithm has been proposed to realize the developed theory. In this algorithm, three criteria have been taken into consideration to be respected when designing the clamping system. These are minimum number of clamps, maximum contrariety of clamping force components with respect to the twists tending to break contact between the workpiece and the locators, and maintenance of workpiece's static stability under different wrenches. The suggested theory and algorithm have been incorporated into a platform already developed by the authors in Python-OCC for computer aided fixture design. The fixturing of three different machining workpieces have been examined for evaluating the capabilities of the suggested theory and algorithm. These workpieces had freeform surfaces which were defined by NURBS formulation. Highlights: Development of mathematics for automated clamping system design for NURBS surfaces. Introduction of contrariety and repelling intensity factors for efficient design. Application of minimum norm principle to stability check needed for NURBS surfaces. Ensuring use of minimum number of clamps to keep contact between part and locators.